Semar Mesem among Santri: A Phenomenological Study of Magical Practices - Sholahuddin Al Ayubi; Ursa Agnia; H.S. Suhaedi; Nouval Syamsu; Kholilullah Kholilullah (Al Qalam, 2025)
This study examines an interesting phenomenon in the world of pesantren: the use of the magical practice "Semar Mesem". Through a qualitative approach, this research seeks to understand this practice’s meaning, purpose, and consequences in pesantren life. The study results show that Semar Mesem is not just a magical practice but also reflects the social and psychological dynamics in the pesantren environment. The practice is influenced by various factors, from internal factors such as self-discovery and social pressure to external factors such as cultural and environmental influences. In this study, religious education is correct and comprehensive in responding to this phenomenon. Religious education is not only limited to theoretical understanding but must also be able to form a strong and critical character. In addition, an open dialogue between Santri, scholars, and the community is also needed to find the right solution to overcome these problems.